Analysis of Patient Safety Culture in Dental and Oral Health Services at RSGM Unimus - Dwi Windu Kinanti Arti; Eka Yunila Fatmasari; Retno Kusniati; Juni Arum Sari (Universitas Aisyah Pringsewu, 2022)
The Dental and Oral Hospital (RSGM) as a part of health care facilities, especially teeth and mouth, do not rule out unexpected events / near-injury events that have an impact on patient safety. The safety incidents at RSGM are only reported when an incident occurs. Solving this problem requires changing the culture of health care from one in which errors are viewed as the result of individual failure to one in which errors are viewed as opportunities to improve from one in which errors are viewed as the system. This study aims to determine the culture of patient safety in dental and oral health services at RSGM Unimus. This type of research is descriptive research with mixed methods research approaches, namely quantitative and qualitative. The study involved a sample of 65 respondents, where the study was conducted from March to April 2020. Quantitative data collection techniques used AHRQ (Agency for Healthcare Research and Quality instrument questionnaire) and qualitative through interviews. The results of the study show that in all dimensions of the AHRQ questionnaire, the highest positive response results are in the very good/strong category, which means that the level of patient safety at RSGM Unimus is already supportive. This study shows that the dissemination of patient safety has not been routinely carried out, errors in communication often occur, reporting only when unexpected incidents occur, and it is necessary to increase feedback between medical personnel and evaluation of intentional or accidental errors that is related to patient safety still needs to be improved. Abstrak: Rumah Sakit Gigi dan Mulut (RSGM) sebagai bagian dari sarana pelayanan kesehatan khususnya gigi dan mulut tidak menutup kemungkinan terjadinya kejadian yang tidak diharapkan/near injury event yang berdampak pada keselamatan pasien. Pelaporan terkait insiden keselamatan hanya di RSGM hanya dilakukan saat terjadi insiden. Masalah ini dapat dipecahkan dengan perubahan budaya keselamatan pasien dimana kesalahan seorang individu dipandang sebagai sebagai peluang untuk memperbaiki sistem. Penelitian ini bertujuan untuk mengetahui budaya keselamatan pasien dalam pelayanan kesehatan gigi dan mulut di RSGM Unimus. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan penelitian metode campuran, yaitu kuantitatif dan kualitatif. Penelitian ini melibatkan sampel sebanyak 65 responden, dimana penelitian dilakukan pada bulan Maret – April 2020. Teknik pengumpulan data kuantitatif menggunakan instrumen AHRQ (Agency for Healthcare Research and Quality instrument kuesioner) dan kualitatif melalui wawancara. Hasil penelitian menunjukkan bahwa pada semua dimensi kuesioner AHRQ, hasil respon positif tertinggi berada pada kategori sangat baik/kuat yang artinya tingkat keselamatan pasien di RSGM Unimus sudah mendukung. Beberapa indikator yang masih perlu ditingkatkan adalah sosialisasi keselamatan pasien yang belum rutin dilakukan, kesalahan komunikasi yang sering terjadi, pelaporan hanya bila terjadi insiden yang tidak diharapkan, perlu peningkatan umpan balik antar tenaga medis dan evaluasi kesengajaan atau kesalahan kecelakaan yang berkaitan dengan keselamatan pasien masih perlu ditingkatkan.